Value Education and Emotional Intelligence: Building A Resilient Generation in the Digital Era to Achieve Sdgs - Muhammad Alfi Syahrin; Khoiriyah; Heri Rifhan Halili; Ammar Wangyee (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to analyze the integration of value-based education and emotional intelligence (EI) in shaping a resilient generation in the digital era to support sustainable education and the achievement of the SDGs. Theoretical framework: Based on the theory of emotional intelligence that emphasizes the management of emotions, empathy, and social skills, as well as the theory of value-based education that places moral character as the main focus of holistic education. Literature review: The literature shows the importance of integrating values and EI in improving students' learning motivation, self-efficacy, academic resilience, and emotional well-being, as well as the role of technology in supporting reflective and value-oriented education. Methods: Using a bibliometric literature analysis of 633 articles from the Scopus database published in 2022–2024 to map trends, key themes, and relationships between variables. Results: Five main clusters were found: the role of technology, sustainability policies, the transformation of educational institutions, teacher contribution and digital literacy, and character education in early childhood. EI has been shown to increase motivation, self-efficacy, academic resilience, and emotional well-being. Implications: There is a need for the development of a holistic education system that integrates values, EI, and empathy-based technologies to support the SDGs. Novelty: Develop a conceptual framework that integrates value education, emotional intelligence, and empathy-based technology in the modern education system to create more humane and reflective learning.